Modified tannic acid-based nanostructures in biomedical fields: New trends from chemistry to biomedical applications - Ashok Kumar Bishoyi; Suhas Ballal; Aman Shankhyan; Shaker Al-Hasnaawei; Krishnakumar Samikan; Rajashree Panigrahi; Girish Chandra Sharma; Aashna Sinha; Manoj Kumar Mishra (Results in Chemistry)
Polyphenols are characterized by multiple phenolic rings in their molecular structure, which are plentiful in the natural environment and can be extracted from various sources, including vegetables, grains, cacao, fruits, tea, legumes, and seeds. Tannic acid is a prime example of a polyphenol with a unique chemical structure. This versatile compound can engage with various natural and synthetic substances, improving performance and addressing specific challenges. The interactions with proteins are flexible and adaptable. As an essential part of supramolecular self-assembly materials, these hybrid or hybrid-like systems assist in developing a range of advanced nanomaterials, which have garnered significant applications in the field of biomedicine due to their outstanding biocompatibility. This review explores the present uses of TA-based materials in medicine. It emphasizes their distinct properties and the possibility of creating novel combinations. This paper centers on the most recent advancements and potential benefits of TA-based technology in antibacterial therapies, drug delivery systems, tumor treatment, and wound healing.